Molecular analysis of the Mycobacterium tuberculosis complex in refrigerated raw milk and geospatial distribution in Brazilian small farms - Alexandrino, Marcela; Gardi, Lívia Vieira; Bertolini, Amanda Bezerra; Flaminio, Ana Paula; Valim, Amanda Corvino; Silva, Laís Pereira da; Leite, Bruna dos Santos; Rangel, Marcos Vinícius; Aires, Isabella Neves; Alencar, Beatriz Januário; Bertozzo, Thainá Valente; Curci, Vera Cláudia Lorenzetti Magalhães; et al. (Food Science and Technology, 2025)
This study reports the investigation of Mycobacterium tuberculosis and Mycobacterium bovis in 102 milk samples from lactating cows, collected directly from cooling tanks of small family farms located in eight municipalities in the state of São Paulo, Brazil. Conventional polymerase chain reaction and real-time polymerase chain reaction techniques were used, as well as spatial analysis. All milk samples tested were negative for M. tuberculosis and M. bovis. Nevertheless, constant epidemiological surveillance of these pathogens is important because raw milk is still widely consumed and has great infectious potential, besides its use in the production of dairy products such as cheese and butter, which are important sources of income for small producers, thus posing risks to public health and farmers’ income.